Epidemiology of Taenia saginata taeniosis/cysticercosis: A systematic review of the distribution in East, Southeast and South Asia - Eichenberger, R.M.; Thomas, Lian F.; Gabriël, S.; Bobić, B.; Devleesschauwer, Brecht; Robertson, L.J.; Saratsis, A.; Torgerson, Paul R.; Braae, U.C.; Dermauw, Veronique; Dorny, P. (Springer, 2020)
Background Taenia saginata is an important zoonotic parasite, causing taeniosis in humans and cysticercosis in bovines, the latter being a significant concern for the global beef industry. Many countries in East, Southeast and South Asia are experiencing rapid economic growth, and an increasing number of people in these countries are dependent on the livestock industry. Currently, however, an overview of the prevalence of T. saginata in this region is lacking. In this review, we analysed the available literature on T. saginata taeniosis and bovine cysticercosis for East, Southeast and South Asia. Methods A systematic review was conducted, based on both published and grey literature. Articles published between 1990 and 2017 were mined for information on the occurrence, prevalence, and geographical distribution of T. saginata taeniosis and bovine cysticercosis in East, Southeast and South Asia. Results The presence of T. saginata was described in 15 of 27 countries of the region, including Afghanistan, Cambodia, China, India, Indonesia, Japan, Lao PDR, Malaysia, Mongolia, Nepal, Pakistan, Philippines, South Korea, Thailand and Vietnam. The only country that reported an absence of T. saginata is Japan, although sporadic reports of imported cases and unconfirmed reports of autochthonous infections were identified. Nationwide surveys of taeniosis with systematic sample collection and high sample numbers were available for Cambodia, China, Lao PDR, and South Korea, although speciation of Taenia was not always performed. Regional prevalence of taeniosis and bovine cysticercosis in endemic regions ranged between 0.02–42.6%, and 0.76–46.7%, respectively. However, data for bovine cysticercosis were only available for five countries (Japan, Lao PDR, Mongolia, Pakistan and Vietnam). Conclusions The data indicate a widespread occurrence of T. saginata throughout East, Southeast and South Asia. Identification of Taenia spp. in human infections was frequently not performed, leading to gaps in knowledge about the distribution of human tapeworm infections, mainly in regions where different human Taenia species co-occur. A high prevalence of T. saginata taeniosis and bovine cysticercosis may reflect insufficiencies in sanitation, limited health education standards, and insufficient food safety measures. Therefore, there is a need to improve local surveillance, notification, and overall control systems.